Climate and limited soil development constrain the distribution of the highest alpine grassline: Insights from a transplanting and warming experiment - Pengfei Ma; Haoze Zhang; Haijuan Wei; Guangshuai Cui; Zhaoheng Deng; Wanglin Zhao; Xinru Zhang; Ying Guo; Liu Yang; Lin Zhang (CATENA, 2026)

Experimental and numerical analysis on two-way hull–propeller coupled effect of a fully-actuated AUV - Tian Xia; Shuo Liu; Tao Wang; Jiangyang Li; Wanglin Lin; Bingbing Zhang; Yong Cai; Wen Xu (Ocean Engineering, 2025)

Parameter Identification of an Unmanned Sailboat Combining Experiments and Numerical Analysis - Yifan Chen; Shuo Liu; Tian Xie; Zhaozhao Zhang; Yu Zhang; Wanglin Lin; Kaiyou Jiang; Tao Wang (Journal of Marine Science and Engineering, 2024)
It is meaningful to develop an accurate model to predict the dynamical motion of an unmanned sailboat. Considering cost and convenience, this work proposes a parameter identification method based on the combination of experiments and numerical analysis. Firstly, a free-running trial is carried out by utilizing the propellers on the studied sailboat to acquire real navigation information. Secondly, particle swarm optimization (PSO), which is highly efficient and easily implemented, is designed to acquire the hydrodynamic parameters of the sailboat’s hull. At the same time, the aerodynamic parameters of the sail are acquired by computational fluid dynamics (CFD) simulation. Finally, a three degree-of-freedom (DOF) model is established, the effectiveness of which is verified through comparisons between sea trials and simulation. The results prove that this parameter identification method has the desired accuracy and reliability.

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

Precipitation and anthropogenic activities regulate the changes of NDVI in Zhegucuo Valley on the southern Tibetan Plateau - Wanglin Zhao; Hengying Wang; Huifang Zhang; Lin Zhang (Journal of Mountain Science, 2024)